Penerapan Media Pembelajaran Interaktif Berbasis Multimedia Untuk Meningkatkan Pemahaman Konsep Matematika Peserta Didik Sekolah Dasar - Adella Shifa Okvita Fiani; Naya Amelia Wibowo; Yohanes Anando Aryo Andoyo; Nela Rofisian (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to optimize multimedia-based interactive learning media to improve elementary school students' understanding of mathematical concepts. The background to this research is the challenges faced by students in understanding mathematical concepts due to conventional learning methods which are limited to verbal explanations and practice questions in textbooks, especially on the topic of fractions. Using a descriptive qualitative approach, this research was prepared by collecting interview data at SD N 2 Mlese Gantiwarno Klaten. The research results show that the use of interactive learning media that involves visual and audio elements can foster students' motivation and understanding in learning mathematics. This approach has the potential to create a more interesting learning atmosphere, increase student absorption, and provide learning facilities that are more effective, relevant, and responsive to educational needs in the digital era.